2008
DOI: 10.1111/j.1365-2443.2008.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Clock‐dependent and independent transcriptional control of the two isoforms from the mouse Rorγgene

Abstract: Accumulating evidence indicate that molecular mechanisms generating circadian rhythms display some degree of tissue‐specificity. More specifically, distinct patterns of expression for nuclear receptors of the ROR family indicate that the transcriptional control of the clock gene Bmal1 differs among tissues. This study aims to investigate the expression of Rorγisoforms (Rorγ and Rorγt) and characterize the molecular mechanisms underlying their tissue‐specific expression. The expression of Rorγ isoforms was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 54 publications
8
20
0
Order By: Relevance
“…Figure 1J shows that particularly RORγ1 , the only RORγ isoform expressed in liver, showed a robust oscillatory pattern of expression, while RORα1 , which is expressed at low levels, has a moderate and RORα4 , which in liver is the predominant α isoform, exhibited a weak oscillatory pattern consistent with earlier observations (16,20,52). Loss of RORγ or RORα expression had little effect on the circadian expression of RORα1 or α4 and RORγ1 mRNA, respectively, suggesting that RORα and RORγ are regulated independently from each other (Figure 1J).…”
Section: Resultssupporting
confidence: 88%
“…Figure 1J shows that particularly RORγ1 , the only RORγ isoform expressed in liver, showed a robust oscillatory pattern of expression, while RORα1 , which is expressed at low levels, has a moderate and RORα4 , which in liver is the predominant α isoform, exhibited a weak oscillatory pattern consistent with earlier observations (16,20,52). Loss of RORγ or RORα expression had little effect on the circadian expression of RORα1 or α4 and RORγ1 mRNA, respectively, suggesting that RORα and RORγ are regulated independently from each other (Figure 1J).…”
Section: Resultssupporting
confidence: 88%
“…Since Rorγt is not under circadian control but could be regulated by transcription factors that bind E-boxes it could explain the up regulation of Bmal1 . Furthermore, up-regulation of StAR could also be explained by the down-regulation of Per1 [69]. Per1 has previously been shown to be down regulated in Crem −/− mice [68] also confirming our results.…”
Section: Discussionsupporting
confidence: 91%
“…ChIP-Seq analysis showing an association of RORγ with the regulatory region of several of these genes, including Insig2a and Elovl3 , suggested that these genes are regulated directly by RORγ. Studies showing that the diurnal expression of RORγ is directly regulated by the circadian clock machinery (15,16,18), together with our findings that the phase of the diurnal pattern of expression of several of these genes closely follows that of RORγ, suggest a connection between the diurnal regulation of these metabolic genes, the rhythmic expression of RORγ, and the circadian clock. These observations are further consistent with our hypothesis that RORγ functions as a transcriptional mediator that regulates the rhythmic expression of certain metabolic genes downstream of the clock machinery (Figure 7C).…”
Section: Discussionsupporting
confidence: 72%